2008
DOI: 10.1017/s0265021508003694
|View full text |Cite
|
Sign up to set email alerts
|

The postoperative analgesic efficacy of intraperitoneal tramadol compared to normal saline or intravenous tramadol in laparoscopic cholecystectomy

Abstract: Intravenous tramadol provides superior postoperative analgesia in the early postoperative period after laparoscopic cholecystectomy compared with an equivalent dose of tramadol administered intraperitoneally and with normal saline in patients undergoing laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…16 Mean systolic BP and RR were lower in group I than in group II at all time intervals but the difference is significant statistically at 0 and 4 hours attributed to better pain control in early postoperative period. As there was no differences in the incidence of adverse effect, so tramadol can be used safely at doses as in our study intraperitoneally, which can be correlated with study done by Akinci et al 13 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16 Mean systolic BP and RR were lower in group I than in group II at all time intervals but the difference is significant statistically at 0 and 4 hours attributed to better pain control in early postoperative period. As there was no differences in the incidence of adverse effect, so tramadol can be used safely at doses as in our study intraperitoneally, which can be correlated with study done by Akinci et al 13 …”
Section: Discussionsupporting
confidence: 90%
“…The sample size has been calculated based on the study, 13 where mean pain score of the normal saline (3.9 ± 2.7) has been consulted. The sample size per group has been calculated to be 50 with 5% level of significance.…”
Section: Methodsmentioning
confidence: 99%
“…Akinci et al [9] showed that I.V tramadol produced superior post-operative analgesia compared with equivalent dose of Tramadol. On the contrary, Memis et al [10] found that intraperitoneal Tramadol and Bupivacaine are very effective for post-operative analgesia in patients undergoing Laparoscopic tubal ligation.…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Akinsi et al 25 concluded that intravenous tramadol provides superior postoperative pain relief as compared to intraperitoneal administration.…”
Section: Discussionmentioning
confidence: 99%